Carrying dreams to the colonizer’s country: the historical experiences of the Algemeene Middelbare School A-1 Eastern literature intellectual network in crossing oceans in the colonial era - Heri Priyatmoko; Singgih Tri Sulistiyono; Dhanang Respati Puguh (Cogent Arts & Humanities)
This article aims to examine the historical experience of the intellectual network of the major of Eastern Literature at the Algemeene Middelbare School (AMS) A-1 sailing across the oceans to study in the Netherlands from the perspective of maritime and technological history. Using the historical method, it is known that alumni from the AMS A-1 have realized this dream of becoming an intellectual by continuing their studies in law and philology in the colonizer’s country. The young natives put their lives on the line and held back their longing, determined to board a ship from the Dutch East Indies to the Netherlands for a month. It is proven that the historical movement of AMS A-1 intellectuals is supported by technological and international shipping networks. This is shown in both egodocuments and newspaper sources in this study. The AMS A-1 network obtained information from mass media to determine the type of ship they should travel with. While crossing the ocean, undergraduates and teachers from the AMS A-1 experienced social stratification on the ship’s deck. Class I, II, and III sorting applied based on social and economic groups. Thus, ships became not only a medium for spreading and achieving new knowledge but also a place to reinforce colonial European culture, which was also a reference on the ship. In historiography, this study fills the void in maritime history, which highlights how intellectual passengers changed their destiny by studying abroad. Research on school networks here is limited by focusing on the ocean and a single network, yet it opens up the field for further research on the dynamics of transnational educational networks and their impact on colonial and postcolonial society.